Robert A. Taft - Kennedy, John F. (John Fitzgerald), 1917-1963 (Social Studies School Service, 1983)
Dramatizes Senator Robert A. Taft's courage in condemning the Nuremberg war crimes trials because of his belief that it was unjust to hold the trials under an ex post facto law. Evaluates Taft's judgment in terms of equal justice under law and the concept of international law.